2019
DOI: 10.1038/s12276-019-0227-1
|View full text |Cite
|
Sign up to set email alerts
|

LFA-1 (CD11a/CD18) and Mac-1 (CD11b/CD18) distinctly regulate neutrophil extravasation through hotspots I and II

Abstract: Precise spatiotemporal regulation of leukocyte extravasation is key for generating an efficient immune response to injury or infection. The integrins LFA-1(CD11a/CD18) and Mac-1(CD11b/CD18) play overlapping roles in neutrophil migration because they bind the same as well as different ligands in response to extracellular signaling. Using two-photon intravital imaging and transmission electron microscopy, we observed the existence of preferred sites for neutrophil entrance into the endothelial cell monolayer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
66
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 42 publications
7
66
0
1
Order By: Relevance
“…Overall, we found that NMIIA regulates integrin-based adhesion stability during neutrophil arrest, possibly via different nonexclusive mechanisms, as previously reported (Vicente-Manzanares et al, 2009). We document that Itgb2 redistributes from a dispersed intracellular pool to a defined area of the neutrophil surface that is juxtaposed to the inflamed endothelium (adhesion ring), consistent with previous in vivo and in vitro studies (Hyun et al, 2019;Jones et al, 1988;Shaw et al, 2004). At this stage, we cannot resolve whether Itgb2 clusters observed at the adhesion ring-like structures are formed through lateral diffusion or rapid internalization and recycling back to the PM.…”
Section: Resultssupporting
confidence: 91%
“…Overall, we found that NMIIA regulates integrin-based adhesion stability during neutrophil arrest, possibly via different nonexclusive mechanisms, as previously reported (Vicente-Manzanares et al, 2009). We document that Itgb2 redistributes from a dispersed intracellular pool to a defined area of the neutrophil surface that is juxtaposed to the inflamed endothelium (adhesion ring), consistent with previous in vivo and in vitro studies (Hyun et al, 2019;Jones et al, 1988;Shaw et al, 2004). At this stage, we cannot resolve whether Itgb2 clusters observed at the adhesion ring-like structures are formed through lateral diffusion or rapid internalization and recycling back to the PM.…”
Section: Resultssupporting
confidence: 91%
“…Interestingly, we observed that once a neutrophil used a JMP to cross the endothelium, other neutrophils followed this path and used the same exit-site ( Figure 2E). This was in line with an increase in endothelial JMP dynamics at exit-sites after the first neutrophil crossed ( Figure 2F), in line with a recent publication by Hyun and colleagues (Hyun et al, 2019). These data suggest that endothelial JMPs can function as exit-recognition sites that are reinforced by transmigration.…”
Section: Neutrophils Prefer Local Exit-sitessupporting
confidence: 91%
“…(Figure 1H). In addition, we observed the presence of multiple hotspots (55) in the wall of high endothelial venules (HEVs), suggesting a relevant role of these areas in the observed recruitment (Figure 1G; Supplementary Movie 1). To confirm this observation, we performed electron microscopy in a PLN HEV, which clearly showed neutrophils associated with the blood vessel endothelium as early as 2 h p.v.…”
Section: Resultsmentioning
confidence: 92%